Screening and early detection efforts in lung cancer. Issue 9 (13th January 2015) - Kanodra, Neeti M.; Silvestri, Gerard A.; Tanner, Nichole T.
<x xml:space="preserve">Abstract</x> Lung cancer is the leading cause of cancer‐related death in the United States. Since publication of results from the National Lung Screening Trial, several professional organizations, including the US Preventive Services Task Force, have published guidelines recommending low‐dose computed tomography for screening in asymptomatic, high‐risk individuals. The benefits of screening include detection of cancer at an early stage when a definitive cure is possible, but the risks include overdiagnosis, false‐positive results, psychological distress, and radiation exposure. The current review covers the scope of low‐dose computed tomography screening, potential risks, costs, and future directions in the efforts for early detection of lung cancer. Cancer 2015;121:1347–1356. © 2015 American Cancer Society.